2019
DOI: 10.1212/wnl.0000000000006694
|View full text |Cite
|
Sign up to set email alerts
|

White matter differences between essential tremor and Parkinson disease

Abstract: ObjectiveTo assess white matter integrity in patients with essential tremor (ET) and Parkinson disease (PD) with moderate to severe motor impairment.MethodsSedated participants with ET (n = 57) or PD (n = 99) underwent diffusion tensor imaging (DTI) and fractional anisotropy, mean diffusivity, axial diffusivity, and radial diffusivity values were computed. White matter tracts were defined using 3 well-described atlases. To determine candidate white matter regions that differ between ET and PD groups, a bootstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 48 publications
2
33
1
Order By: Relevance
“…A somewhat unexpected finding of this study was the absence of significant white matter alterations in patients with ETv and DTv. This is a discrepancy from previous studies that reported white matter changes in the cerebellum, corpus callosum, thalamocortical visual pathways in ET, [48][49][50] as well as the posterior limb of the internal capsule in DTv. 12 Possible explanations may include the stringent criteria for selection of homogeneous patient populations and the methodological constraints, such as differences in diffusion-weighted imaging sequence acquisition and a stringent statistical thresholding employed in this study that might have excluded smaller clusters of between-group differences reported in the previous literature.…”
Section: Discussioncontrasting
confidence: 99%
“…A somewhat unexpected finding of this study was the absence of significant white matter alterations in patients with ETv and DTv. This is a discrepancy from previous studies that reported white matter changes in the cerebellum, corpus callosum, thalamocortical visual pathways in ET, [48][49][50] as well as the posterior limb of the internal capsule in DTv. 12 Possible explanations may include the stringent criteria for selection of homogeneous patient populations and the methodological constraints, such as differences in diffusion-weighted imaging sequence acquisition and a stringent statistical thresholding employed in this study that might have excluded smaller clusters of between-group differences reported in the previous literature.…”
Section: Discussioncontrasting
confidence: 99%
“…Using diffusion kurtosis imaging, Ito et al (90,91) described a ratio of midbrain tegmentum diffusion to pontine crossing tract diffusion to distinguish between patients with PSP, MSA or PD and controls (90,91). Interestingly, Juttukonda et al (92) also found an FA decrease in the pontine crossing tract in patients with essential tremor vs. PD (92).…”
Section: Advanced Diffusion Approachesmentioning
confidence: 99%
“…Electrophysiology, structural magnetic resonance imaging (MRI), diffusion MRI, and positron emission tomography (PET) studies have revealed various abnormalities in cerebello-thalamo-cortico-cerebellar circuits in ET ( 45 , 46 ). Based on that, a recent study revealed the distinctive white matter microstructural values localize to the cerebellar peduncles and thalamo-cortical visual pathways via diffusion tensor imaging (DTI) and fractional anisotropy, suggesting that a cerebello-thalamo (posterior) cortical network rather than a cerebello-thalamo-motor cortical network takes part in ET ( 47 ).…”
Section: Anatomical Network Involved In Relevant Diseasesmentioning
confidence: 99%